Influence of chlorine coordination number on the catalytic mechanism of ruthenium chloride catalysts in the acetylene hydrochlorination reaction: a DFT study. Issue 12 (25th February 2015) - Han, You; Sun, Mengxia; Li, Wei; Zhang, Jinli
Abstract : Among Ru3 Cl9, Ru3 Cl7, Ru5 Cl7, Ru3 Cl3 and Ru3 catalytic models, Ru5 Cl7 performs best. In Ru5 Cl7, the low chloride-coordinated Ru is responsible for activating reactants and adding H to C2 H2, while the high coordinated is responsible for providing Cl to C2 H3 ˙. Abstract : The catalytic mechanism of Ru-based catalysts in the acetylene hydrochlorination reaction has been investigated via the density functional theory (DFT) method. To study the effect of the chlorine coordination number on the catalytic mechanism, Ru3 Cl9, Ru3 Cl7, Ru5 Cl7, Ru3 Cl3 and Ru3 clusters were chosen as the catalytic models. Our results show that the energy barrier for acetylene hydrochlorination on Ru3 Cl9 was as high as 1.51 eV at 458 K. When the chlorine coordination number decreased, the energy barriers on Ru3 Cl7, Ru5 Cl7, Ru3 Cl3 and Ru3 were 1.29, 0.89, 1.01 and 1.42 eV, respectively. On Ru3 Cl9, the H and Cl atoms of HCl were simultaneously added to C2 H2 to form C2 H3 Cl, while the reaction was divided into two steps on Ru3 Cl7, Ru3 Cl3 and Ru3 clusters. The first step was the addition of H atom of HCl to C2 H2 to form C2 H3 ˙, and the second step was the addition of Cl atom to C2 H3 ˙ to form C2 H3 Cl. The step involving the addition of Cl was the rate-controlling step during the whole reaction. On Ru5 Cl7 cluster, there was an additional step before the steps involving the addition of H and Cl: the transfer of H atom from HCl to Ru atom. This step was the rate-controlling step during the reaction of acetylene hydrochlorination on Ru5 Cl7 and its energy barrier was the lowest among all the above-mentioned catalytic models. Therefore, the Ru5 Cl7 cluster played the most predominant role in acetylene hydrochlorination with the largest reaction rate constant k TST of 10 3 .